2018
DOI: 10.3390/ijerph15010159
|View full text |Cite
|
Sign up to set email alerts
|

Association between Work Related Stress and Health Related Quality of Life: The Impact of Socio-Demographic Variables. A Cross Sectional Study in a Region of Central Italy

Abstract: The aim of this work is investigate relationship between health-related quality of life and work-related stress and the impact of gender, education level, and age on this relationship. A cross-sectional study was conducted among workers of various setting in Rome and Frosinone. Work-related stress was measured with a demand–control questionnaire and health-related functioning by SF (short form)-12 health survey. There were 611 participants. Men reported high mental composite summary (MCS) and physical composit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 26 publications
1
33
0
1
Order By: Relevance
“…Previous research concluded that work-related stress is associated and increase an individual's vulnerability to burnout, job satisfaction and physical as well as mental health outcomes (Piko, 2006;Pillay, 2009). Other health problems related to the effects of work stress include: cardiovascular disorders (Li, Loerbroks, Bosma, & Angerer, 2016), gastrointestinal disorders (Huerta-Franco, 2013), musculoskeletal disorders (Nafeesa, Vidhya, Vijayalakshmi, & Rajkumar, 2017), anxiety and depression (Fan, Blumenthal, Watkins, & Sherwood, 2015), work fatigue (Rose et al, 2017), insomnia (Deguchi et al, 2017), alcohol abuse (Moore, Sikora, Grunberg, & Greenberg, 2007), decrease marital quality (Obradović & Čudina-Obradović, 2013) and disruption of social interaction (La Torre et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research concluded that work-related stress is associated and increase an individual's vulnerability to burnout, job satisfaction and physical as well as mental health outcomes (Piko, 2006;Pillay, 2009). Other health problems related to the effects of work stress include: cardiovascular disorders (Li, Loerbroks, Bosma, & Angerer, 2016), gastrointestinal disorders (Huerta-Franco, 2013), musculoskeletal disorders (Nafeesa, Vidhya, Vijayalakshmi, & Rajkumar, 2017), anxiety and depression (Fan, Blumenthal, Watkins, & Sherwood, 2015), work fatigue (Rose et al, 2017), insomnia (Deguchi et al, 2017), alcohol abuse (Moore, Sikora, Grunberg, & Greenberg, 2007), decrease marital quality (Obradović & Čudina-Obradović, 2013) and disruption of social interaction (La Torre et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, being employed is a source of financial security, provides people the opportunity to fulfil a social and family role, and is important for physical and mental health [ 3 , 4 ]. Unemployment means a change in social position, particularly in the family, and is usually perceived as a very stressful life event [ 5 , 6 , 7 ] with relevant consequences for health [ 8 , 9 ]. Precise and commonly shared definitions of employment and unemployment status are lacking and different studies addressed them differently: these include long-term vs. short-term unemployment, or temporary interruptions, and are referred to people of working age (but not student or in training) that are actively looking for work.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the pattern of gender differences with regard to the effect of work stress on cardiovascular disease is not clear [ 27 , 28 ]. Some recent research has suggested gender as an effect modifier of the association between work stress and health [ 62 ]. Furthermore, in psychosocial stress research, particularly among women, it has been suggested that working women are under dual stress from work and from family.…”
Section: Discussionmentioning
confidence: 99%